Activity of CDK4/6 inhibitors and parameters affecting survival in elderly patients in age-subgroups: Turkish Oncology Group (TOG) retrospective study - Seda Kahraman; Mutlu Hizal; Burcin Cakan Demirel; Deniz Can Guven; Ozge Gumusay; Basak Oyan Uluc; Ertugrul Bayram; Burcu Gulbagci; Alper Yasar; Sena Ece Davarci; Eda Eylemer Mocan; Omer Acar; et al. (BMC Cancer)
Abstract Highly selective inhibitors of cyclin-dependent kinase 4 and 6 (CDK4/6is) have emerged as a standart of care for first- and second-line therapies in combination with endocrine therapy (ET) for HR+/HER2- metastatic breast cancer (MBC) patients. It has been reported that combination therapy is more effective than ET alone and is safe in elderly patients as well as young patients. Nevertheless, elderly and very old patients with HR+/HER2-MBC treated with CDK4/6 inhibitor (CDK4/6i) combinations are relatively underrepresented in randomized controlled trials. To contribute to the literature, we investigated the real-world efficacy, factors associated with survival and the rates of adverse events (AEs) of the treatment with palbociclib or ribociclib plus ET in the HR+/HER2- MBC patient cohort over the age of 65 for age subgroups. In this retrospective study, 348 patients were divided into subgroups: 65–69 years old, 70–79 years old and 80 years and older. Median PFS (mPFS) for whole group was 18.3 (95% CI,14.3–22.3) months. There was no significant difference in mPFS between age groups (p = 0.75). The estimated median OS (mOS) was 39.5 (95% CI, 24.9–54.1) months and there was no significant difference between age groups (p = 0.15). There was a meaningfull numerical difference that did not reach statistical significance in patients who received CDK4/6i treatment as the first line for MBC. Grade 3–4 AEs were reported in 42.7% for the entire group, and neutropenia was the most common (37.3%). It can be concluded that combination therapy with palbociclib or ribociclib with an ET partner has similar efficacy and is safe among subgroups of older patients diagnosed with HR+/HER2-MBC.